Організація електронного документообігу у Департаменті містобудування Львівської міської ради - Ільченко, Вероніка; Марковець, Олександр (Видавництво Львівської політехніки, 2016)
An article about the organization of electronic document management in the Department of City Planning of Lvivska Miska Rada. Considered the question of the importance of electronic documents and system of electronic document "Alfresco".
Keywords: Львівська міська рада; Департамент містобудування; електронний документообіг; система "Alfresco"